Trade‐offs among agronomic, energetic, and environmental performance characteristics of corn and prairie bioenergy cropping systems. Issue 1 (4th January 2014) - Jarchow, Meghann E.; Liebman, Matt; Dhungel, Shashi; Dietzel, Ranae; Sundberg, David; Anex, Robert P.; Thompson, Michael L.; Chua, Teresita
Abstract Cellulosic bioenergy production provides opportunities to utilize a range of cropping systems that can enhance the multifunctionality of agricultural landscapes. In a 9‐ha field experiment located on fertile land in Boone County, IA, USA, we directly compared a corn‐soybean rotation harvested for grain, continuous corn harvested for grain and stover, continuous corn harvested for grain and stover with a rye cover crop, newly reconstructed prairie harvested for biomass and fertilized with nitrogen, and unfertilized newly reconstructed prairie harvested for biomass. Comparisons were made using four performance indicators: harvestable yield, net energy balance (NEB), root production, and nutrient balances. We found trade‐offs among systems in terms of the measured performance indicators. Continuous corn systems were the highest yielding, averaging 13 Mg ha−1 of harvested biomass (grain plus stover), whereas fertilized and unfertilized prairies produced the least harvested biomass at 8.8 and 6.5 Mg ha−1, respectively. Mean NEBs were highest in continuous corn systems at 45.1 GJ ha−1, intermediate in the corn‐soybean rotation at 28.6 GJ ha−1, and lowest in fertilized and unfertilized prairies at 11.4 and 10.5 GJ ha−1, respectively. Concomitant with the high yields of the continuous corn systems were the large nutrient requirements of these systems compared to the prairie systems. Continuous corn with rye required three times more nitrogen inputs than fertilized prairie. Root production, on the other hand, was on average seven times greater in the prairie systems than the annual crop systems. On highly fertile soils, corn‐based cropping systems are likely to play an important role in maintaining the high productivity of agricultural landscapes, but alternative cropping systems, such as prairies used for bioenergy production, can produce substantial yield, require minimal externally derived inputs, and can be incorporated into the landscape at strategic locations to maximize the production of other ecosystem services.